Analysis of Irregular Shaped Tall Structure Considering Shear Wall at different Positions using Analysis Tool Staad.Pro - Jain, Shelja; Sathbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2020)
Earthquake is a form of disaster which occurs due to Natural or Man-made errors resulting in extreme damages to human civilization and any form of structure created by us. Recent example of such a disastrous earthquake was seen in our neighbouring country Nepal, resulting in massive destruction to the entire country destroying its economy and placing a setback of more than 10 years. It was such an unusual disaster, that it is extremely vital for survival to ensure the strength of the structures against seismic forces. In this way, there is persistent research work going on around the world, rotating around the advancement of new and better methods that can be consolidated in structures for better seismic execution. Structures designed considering exceptional methods to resist such forces and seismic forces have a considerably higher cost of development than ordinary structures, yet for prosperity against tension on the structure under seismic forces, it is fundamental. In this study we are analysing four different cases of a tall structure G+14 considering shear wall at different positions, in this study we will compare a conventional structure with shear wall structure considering P-delta analysis as per I.S. 1893-I:2002.